2018
DOI: 10.1371/journal.pone.0194391
|View full text |Cite
|
Sign up to set email alerts
|

Food hygiene practices and its associated factors among model and non model households in Abobo district, southwestern Ethiopia: Comparative cross-sectional study

Abstract: BackgroundIn developing country most of human infectious diseases are caused by eating contaminated food. Estimated nine out ten of the diarrheal disease is attributable to the environment and associated with risk factors of poor food hygiene practice. Understanding the risk of eating unsafe food is the major concern to prevent and control food borne diseases. The main goal of this study was to assessing food hygiene practices and its associated factors among model and non model households at Abobo district.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 0 publications
6
20
4
Order By: Relevance
“…Likewise the other factors like whether the patients had intravenous injection and whether the antibiotics treatment was given by the patients was included in the study and found significant with 1% and 5% level of significance. Other previous studies are also consistent with this result [7][8][9].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise the other factors like whether the patients had intravenous injection and whether the antibiotics treatment was given by the patients was included in the study and found significant with 1% and 5% level of significance. Other previous studies are also consistent with this result [7][8][9].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies revealed that the variable was signi cant factors for cholera outbreak [5,6] Likewise the other factors like whether the patients had intravenous injection and whether the antibiotics treatment was given by the patients was included in the study and found signi cant with 1% and 5% level of signi cance. Other previous studies are also consistent with this result [7][8][9] The results of cut1 (-1.738741) in Table 2 above refers to the estimated cut-point on latent variable to differentiate no dehydrated from some dehydrated and severe dehydrated when the value of all predictors are evaluated at their reference categories. Whereas cut2 (.186633) is the estimated cut-point used to differentiate some dehydrated from no dehydrated and severe dehydrated keeping the factors to be at their reference.…”
Section: Discussionsupporting
confidence: 85%
“…The study revealed that, majority (91.4%) of the establishments'' dining room, about two-third (66.7%) of the kitchens and 68.5% of the store room had good and clean sanitary conditions. Safer food preparation and handling were reported by persons who were females, at least 40 years of age and at least having high school level education in some studies conducted elsewhere [19,20].Majority of the food handlers in our study were found to be males, in the age range between 20 and 35 years and a few of them had reached higher educational level. The reason for more number of young males as food handlers' might be due to the higher unemployment rate in other sectors of the country.…”
Section: Discussionsupporting
confidence: 43%